Application of the K-Means Cluster for the Classification of Disadvantaged Districts/Cities in Maluku Province - Muhammad Yahya Matdoan; Faraniena Yunaeni Risdiana; Gabriella Haumahu (JRST (Jurnal Riset Sains dan Teknologi), 2022)
Maluku Province is still the 4th poorest province in Indonesia. This is due to the disparity in development between the provincial and district centers, cities and villages as well as government work programs that are not implemented evenly. To overcome and evaluate these problems, it is necessary to plan or study the classification of underdeveloped regions, namely by grouping districts/cities based on indicators of nderdeveloped areas. This research was conducted using secondary data obtained from the Central Statistics Agency (BPS) of Maluku Province. The method used in this study is to use the K-Means Cluster analysis method. The results of the study indicate that there are 2 classifications of underdeveloped and undeveloped areas in Maluku Province. Cluster 1 consists of Tanimbar Islands Regency, Southeast Maluku Regency, Central Maluku Regency, Buru Regency, Aru Islands Regency, West Seram Regency, Eastern Seram Regency, Southwest Maluku Regency, South Buru Regency and Tual City. In Cluster 2 there is only one area, namely Ambon City.